2001
DOI: 10.1037/1099-9809.7.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Holding on and letting go: Identity and acculturation among Chinese immigrants.

Abstract: This study addresses the general question of whether ethnic identity and general acculturation would prove unique discriminators of quality of life for Chinese immigrants. Eighty-three Chinese immigrants served as participants. Survey data were collected regarding acculturation, Asian identity, and quality of life; observers provided ratings of certain home environment characteristics; and participants responded to open-ended interview questions about their immigration experiences that allowed for qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 28 publications
3
60
0
Order By: Relevance
“…Questions asked students about their willingness to, "have American and Chinese friends in schools," "believe you are part of America," "speak English with Chinese friends," "use English with American friends to learn about American culture," and "encourage teachers to talk about the American and Chinese cultures equally in my classes." These domains were also borne out in the previously cited research (Lee, 1999(Lee, , 2002Lieber et al, 2001;Tong et al, 2006;Yeh, 2002Yeh, , 2003Yeh et al, 2008) that focused on the cultural adjustments, changing cultural identity, and the impact these adjustments and changes may have on producing or reducing acculturative stress.…”
Section: Instrumentationmentioning
confidence: 90%
See 1 more Smart Citation
“…Questions asked students about their willingness to, "have American and Chinese friends in schools," "believe you are part of America," "speak English with Chinese friends," "use English with American friends to learn about American culture," and "encourage teachers to talk about the American and Chinese cultures equally in my classes." These domains were also borne out in the previously cited research (Lee, 1999(Lee, , 2002Lieber et al, 2001;Tong et al, 2006;Yeh, 2002Yeh, , 2003Yeh et al, 2008) that focused on the cultural adjustments, changing cultural identity, and the impact these adjustments and changes may have on producing or reducing acculturative stress.…”
Section: Instrumentationmentioning
confidence: 90%
“…Some studies of Asian adolescents (Lee, 1999(Lee, , 2002Lieber, Chin, Nihira, and Mink, 2001;Yeh, 2002Yeh, , 2003Yeh et al, 2008) have taken a psychosocial approach and examined critical indicators of cultural adjustment that include redefining one's ethnic identity, the extent of cultural interaction, maintaining primary language and culture, and the effects of acculturative stress. These studies found that cultural adaptation, not assimilation (Lee, 1999(Lee, , 2002, intercultural interaction (Lieber et al, 2001), and intercultural competence (Yeh, 2002(Yeh, , 2003Yeh et al, 2008) lessened the anxiety of acculturative stress. These conclusions may have relevance to the present study, as Chinese students are developing a cross-cultural identity that involves cultural adjustment behaviors cited by these researchers.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…There is a plethora of research on identity issues in the process of acculturation to North America, including studies on the following ethnic groups: Vietnamese (Allendoerfer, 1999), Filipino (Nadal, 2004), Chinese (Lieber, Chin, Nihira, & Mink, 2001), Latino (Cardona, Busby, & Wampler, 2004), and Haitian (Bachay, 1998). Acculturation in other parts of the world has also been studied: Norwegian Sami (Kvernmo & Heyerdahl, 2004), Russians in Finland (Jasinskaja-Lahti & Liebkind, 1999), and Ethiopian Jews in Israel (Berhanu, 2005).…”
Section: Sociocultural Theory and Identity Constructionmentioning
confidence: 97%
“…This suggests there are different mechanisms through which family and peer groups affect mental well-being. Data on a metropolitan sample of Chinese Americans showed a significant, negative association between depression and family support, and no significant effect of support from non-family members (Lieber et al 2001). In addition, a study of Asian Americans also found discrepancies in the effects of familial or peer strains (Sangalang and Gee 2012).…”
Section: Predictors Of Depression Among Chinese Americansmentioning
confidence: 99%
“…However, the generalizability of the study results were limited because the study samples were adolescents or college-aged individuals (Greenberger and Chen 1996;Almeida et al 2011), Asian Americans rather than Chinese Americans (Sangalang and Gee 2012), regional community data (Lieber et al 2001), or the elderly (Wu et al 2004). Furthermore, no study has compared the effects of …”
Section: Predictors Of Depression Among Chinese Americansmentioning
confidence: 99%